2020
DOI: 10.1186/s12885-020-6591-3
|View full text |Cite
|
Sign up to set email alerts
|

A decrease in brown adipose tissue activity is associated with weight gain during chemotherapy in early breast cancer patients

Abstract: Background: A decrease in thermogenesis is suspected to be implicated in the energy expenditure reduction during breast cancer treatment. This study aimed to investigate the impact of chemotherapy on the metabolic activity of brown adipose tissue (BAT) and the link with weight variation.Methods: This was an ancillary analysis of a multicentre trial involving 109 HER2+ breast cancer patients treated with neoadjuvant chemotherapy. A centralised review of 18 F-FDG uptake intensity (SUV max ) in specific BAT regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
1
9
0
2
Order By: Relevance
“…Repeated TZM treatment was associated with profound weight loss. Again, this finding is in tandem with previous studies that have reported similar weight loss in patients on TZM treatment ( Hajjaji et al, 2014 ) although the TZM has been reported to have variable effects of body weight pattern in cancer patients on TZM treatment ( Winkels et al, 2014 ; Reijers and Burggraaf, 2015 ; Ginzac et al, 2020 ). However, oral pretreatment with ADP, LSP, VAL and their fixed-dose combinations further induced weight reduction in the face of TZM chemotherapy highlighting the weight loss potential of these antihypertensive drugs and their fixed-dose combinations which were probably mediated via plasma norepinephrine, insulin, and leptin inhibitions, and these were previously reported in the obese hypertensive patients on prolonged amlodipine, lisinopril, valsartan and fixed-dose amlodipine–valsartan combination use ( Masuo et al, 2001 ; Villecco et al, 2004 ).…”
Section: Discussionsupporting
confidence: 88%
“…Repeated TZM treatment was associated with profound weight loss. Again, this finding is in tandem with previous studies that have reported similar weight loss in patients on TZM treatment ( Hajjaji et al, 2014 ) although the TZM has been reported to have variable effects of body weight pattern in cancer patients on TZM treatment ( Winkels et al, 2014 ; Reijers and Burggraaf, 2015 ; Ginzac et al, 2020 ). However, oral pretreatment with ADP, LSP, VAL and their fixed-dose combinations further induced weight reduction in the face of TZM chemotherapy highlighting the weight loss potential of these antihypertensive drugs and their fixed-dose combinations which were probably mediated via plasma norepinephrine, insulin, and leptin inhibitions, and these were previously reported in the obese hypertensive patients on prolonged amlodipine, lisinopril, valsartan and fixed-dose amlodipine–valsartan combination use ( Masuo et al, 2001 ; Villecco et al, 2004 ).…”
Section: Discussionsupporting
confidence: 88%
“…3b). Current data concerning the association between cancer therapy and BAT are controversial, as some studies indicate that chemotherapy is associated with lower BAT prevalence or activity, while another study reported that the antimetabolite cytarabine may actually have an activating effect 10,[15][16][17] . To assess potential effects of treatment, cancer therapies were grouped into ten categories (Supplementary Table 5); only patients who had their first scan designated as the index scan were compared.…”
mentioning
confidence: 99%
“…As noted above, increased expression of the BAT-associated protein UCP-1 in PAT is negatively associated with RCC prognosis [46]. Previously, studies have associated decreased BAT and UCP-1 activity with weight gain in breast cancer patients and high-fat-fed murine models, respectively [77, 78]. Thus, it will be interesting to further elicit the role of brown fat in the RCC-associated obesity paradox.…”
Section: Discussionmentioning
confidence: 98%